Adaptasi Kepemimpinan Transformasional dalam Pendidikan Islam di Era Transformasi Kelembagaan - Fikri Abdul Aziz; Muh. Hanif (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study analyzes the adaptation of transformational leadership in the process of institutional transformation at Pesantren Daarul Muta’allimin Ciamis. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that the leadership of the kiai does not merely function as traditional charismatic authority but evolves into an adaptive leadership model that integrates moral exemplarity, visionary communication, intellectual stimulation, and individualized consideration as strategies for strengthening pesantren management. The main finding underscores that transformational leadership serves as a key mechanism in bridging pesantren traditions with the demands of modern educational governance, particularly in program development and the preparation for establishing formal educational institutions. Theoretically, this study extends the discourse on Islamic educational leadership by positioning transformational leadership as a model for pesantren institutional adaptation. Practically, the findings offer strategic references for pesantren management in responding to institutional change while preserving Islamic identity.